2012
DOI: 10.1136/thoraxjnl-2012-202678.102
|View full text |Cite
|
Sign up to set email alerts
|

S97 Is an Increased Tendency to Clot a Risk Factor For Developing Idiopathic Pulmonary Fibrosis?

Abstract: Background The aetiology of idiopathic pulmonary fibrosis (IPF) remains poorly understood. Recent animal studies and epidemiological data have suggested that activation of the coagulation cascade in the lung may have an important role in the pathogenesis of IPF. Methods We recruited incident cases of physician diagnosed IPF from five teaching hospitals and eight district general hospitals in England and Wales. Age and sex matched general population controls were recruited from the same region. Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…10 Furthermore, as IPF is usually diagnosed in secondary care, it seems unlikely that a record of this diagnosis will be found in primary care records without confirmation from secondary care. The age distribution of cases with IPF in this study is similar to other population based cohorts of IPF, [12][13][14][15][16] providing reassurance of the validity of diagnosis of IPF in these data. In addition, a study by Fell and colleagues demonstrated that age is a strong predictor of IPF in patients with an atypical Usual Interstitial Pneumonia (UIP) radiographic pattern, whereby individuals over 65 years had 89% specificity for confirming IPF on lung biopsy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…10 Furthermore, as IPF is usually diagnosed in secondary care, it seems unlikely that a record of this diagnosis will be found in primary care records without confirmation from secondary care. The age distribution of cases with IPF in this study is similar to other population based cohorts of IPF, [12][13][14][15][16] providing reassurance of the validity of diagnosis of IPF in these data. In addition, a study by Fell and colleagues demonstrated that age is a strong predictor of IPF in patients with an atypical Usual Interstitial Pneumonia (UIP) radiographic pattern, whereby individuals over 65 years had 89% specificity for confirming IPF on lung biopsy.…”
Section: Discussionsupporting
confidence: 83%
“…It is possible, however, that IPF and ischaemic heart disease share other aetiological risk factors. Studies have suggested that people with IPF have an increased tendency to clot, 14,27,28 and have higher Factor VIII levels than the general population. 14 Previous studies have also demonstrated that elevated Factor VIII levels are associated with an increased risk of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for our finding include 1) IPF increasing the risk of VTE, and 2) a prothrombotic state leading to the development of IPF and VTE. This study supports the hypothesis that activation of the coagulation cascade may be involved in the pathogenesis of IPF [2,7]. …”
supporting
confidence: 89%
“…Possible explanations for our finding include 1) IPF increasing the risk of VTE, and 2) a prothrombotic state leading to the development of IPF and VTE. This study supports the hypothesis that activation of the coagulation cascade may be involved in the pathogenesis of IPF [2,7]. @ERSpublications People with IPF have higher incidence rates of venous thromboembolism and are more likely to be prescribed warfarin…”
supporting
confidence: 75%